PERAN PRODUKTIVITAS KAPITAL DAN TENAGA KERJA SERTA PERUBAHAN TEKNOLOGI DALAM PERTUMBUHAN INDUSTRI MANUFAKTUR DI JAWA TIMUR - Nurul Istifadah (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2012)
This paper aims to calculate and analyze the contribution of productivity of production factors capital andlabor and technology in manufacturing output growth in East Java. The role of technology in the productionprocess referred to as Total Productivity Factor (TPF). Analysis techniques used in this paper is the Residumethod, namely the difference between the growths in total output minus total productivity of factors ofproduction.The results showed that the majority of East Java’s manufacturing industry is labor-intensive industrieswith the technology that is not capital intensive. Thus, the strategy and policy development is the mobilizationof manpower and develop appropriate technology which does not absorb much capital. However, this labormobilization policy needs to consider enactment of the law of diminishing returns that can lower the marginalproductivity of manufacturing output in East Java.Keywords: Manufacturing industry, the residual method, the productivity of factors of production, total factorproductivity